THE USE OF VENN DIAGRAM TECHNIQUE FOR TEACHING DESCIRPTIVE TEXT READING - Malasari, .; Salam, Urai; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract : This research was conducted a pre experimental study to know how significant of Venn Diagram Technique for teaching descriptive text. This study was conduct on the second grade students of SMA Negeri 2 Sungai Raya in academic year 2015/2016. In this research,  the researcher propose a technique. The name’s Venn Diagram technique that focus on the similarities and the differences between two text of descriptive text .The data of study was derived from pre-test and pos- test. The sample is 28 students in XI IPA 1 . The finding of research show that the student’s achievement in reading comprehension got significantly improved. The result of the research was compare from the pre-test  score 68,77and the post- test score 81,96. Furthermore the effect size of the significant improvement of the treatment was 1,95. It is categorized as highly effective since it is higher than 0,80 in the highly effective criteria. Keywords : Venn diagram technique, Descriptive text, Reading Abstrak : penelitian ini dilakukan dengan menggunakan studi pre eksperimen untuk mengetahui seberapa signifikan menggunakan tehnik diagram Venn dalam mrngajar teks deskriptif. Studi ini dilakukan pada siswa kelas XI SMA Negeri 2 Sungai Raya tahun ajaran 2015/2016. Dalam penelitian ini, peneliti mengusulkan sebuah tehnik. Nama tehnik tersebut yaitu tehnik Diagram Venn yang fokus pada persamaan dan perbedaan antara dua buah teks deskriptif. Data pada studi ini berasal dari pre-tes dan post-tes. Sampelnya adalah 28 siswa dari kelas XI IPA 1. Hasil penelitian menunjukkan bahwa prestasi siswa dalam memahami bacaan meningkat secara signifikan. Hasil penelitian ini membandingkan nilai dari pre-test 68,77 dan nilai post-test 81,96. Selanjutnya ukuran efek dari peningkatan yang signifikan dari perlakuan adalah 1,95. Itu dikategorikan sebagai sangat efektif karena lebih tinggi dari 0,80 dalam kriteria sangat efektif. Kata Kunci : Tehnik Diagram Venn, Teks Deskriptif, membaca